Doniphan, Doniphan County - Masters, Peter (Kansas State University, The Chapman Center for Rural Studies, 2013)
This history is about the river town of Doniphan, located in Wayne Township of Doniphan County, Kansas. A combination of topographical and political factors propelled the early growth of Doniphan .the included material is based on a variety of sources including: maps, multiple written histories, photographs, and an interview.
Peter Masters, “Doniphan, Doniphan County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/124.
Keywords: Bleeding Kansas; Doniphan County; Jim Lane; Benedictine; Wayne Township; Independence Creek